Gender and intergenerational support in East Asian families - Kan, M-Y; Zhou, M (Routledge, 2022)
This review essay summarizes recent research on the topics of gender inequalities, family obligations, and intergenerational support in East Asia. We introduce four papers featured in a special issue published in 2021 and 2022 in this journal. We conclude by highlighting the continual importance of intergenerational support and family obligations in East Asian societies. We foresee that families and gender relations in East Asia will continue to evolve with characteristics of both modern gender egalitarian values and traditional family responsibilities. We call for more research on the topics and recommend that future research should investigate the intersection of gender and other dimensions of social inequality, employ advanced research methods, and examine the impacts of recent policies on gender and family.